Sophronia salaganella sp. n. from the Russian Altai and new data on Palaearctic Sophronia Hübner, [1825] species (Lepidoptera, Gelechiidae) - Šumpich, Jan; Bidzilya, Oleksiy V.; Ponomarenko, Margarita G. (Zootaxa, 2019)
Sophronia salaganella Šumpich & Bidzilya, sp. n., is described based on specimens collected in the mountains of the Altai Republic and Buryatia in Russia. The new species is most similar to S. illustrella (Hübner, 1796) and S. orientalis Li & Zheng, 1998 from which it can be reliably distinguished by characters of the genitalia. Sophronia iciculata Omelko, 1999, syn. n., is a junior synonym of S. orientalis; and S. marginella Toll, 1936, syn. n., is a junior synonym of S. consanguinella Herrich-Schaffer, [1854]. Sophronia alaicella Caradja, 1920 is redescribed, and the adult and the male and female genitalia are illustrated. Sophronia illustrella (Hübner, 1796) is recorded from Russia for the first time. A checklist of Sophronia Hübner, [1825] of the world is provided.